Tax Understanding Factors, Equity Sensitivity and Love of the Money Attitudes On Taxpayer Perceptions Regarding Tax Evasion At KPP Pratama Jember - Cahyandari, Adelia Aji; Nuha, Gardina Aulin; Zulkarnaeni, Ahmad Syahfrudin (West Science Accounting and Finance, 2024)
According to the 2020 State of Tax Justice report, it was stated that Indonesia's position in cases of tax evasion by corporate and individual taxpayers is ranked fourth in Asia after China, India and Japan. The large number of tax evasion cases currently occurring have given rise to various perceptions. These various perceptions are influenced by various factors, including understanding of taxation, equity sensitivity and love of the money attitudes. This research aims to determine the factors of understanding taxation, equity sensitivity, and love of the money attitudes towards taxpayers' perceptions regarding tax evasion at KPP Pratama Jember. This research uses a quantitative approach, with the aim of testing hypotheses. The population in this study are individual taxpayers registered at KPP Pratama Jember. Sampling used purposive sampling. The results of this research show that understanding taxation and love of the money attitudes influence taxpayers' perceptions regarding tax evasion, while equity sensitivity does not influence taxpayers' perceptions regarding tax evasion.